Recent German migration laws: A contribution to fiscal sustainability - Gerrit Manthei (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2020)
The German government recently adopted a large number of changes in migration legislation related to asylum seekers and refugees who have immigrated since 2015. While some reforms may have more socio-political impacts, most also have fiscal implications. This work analyses the effects of individual legislative changes on the German fiscal system based on the established method of generational accounting. The results show that these laws likely will have overall positive effects on future German public finances. They also stress the importance of successful integration in general and the positive financial contributions from the immigration of relatively young, skilled workers.
Keywords: E62; F22; H68; K37; 330; immigration; law reform; fiscal sustainability